2015
DOI: 10.1371/journal.pone.0127558
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Promotes Platelet Apoptosis via JNK-Mediated Mitochondrial Damage: Alleviation by N-Acetylcysteine and N-Acetylcysteine Amide

Abstract: Thrombocytopenia in methotrexate (MTX)-treated cancer and rheumatoid arthritis (RA) patients connotes the interference of MTX with platelets. Hence, it seemed appealing to appraise the effect of MTX on platelets. Thereby, the mechanism of action of MTX on platelets was dissected. MTX (10 μM) induced activation of pro-apoptotic proteins Bid, Bax and Bad through JNK phosphorylation leading to ΔΨm dissipation, cytochrome c release and caspase activation, culminating in apoptosis. The use of specific inhibitor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 53 publications
3
38
0
1
Order By: Relevance
“…Moreover, isoliensinine-induced apoptosis in human breast cancer cells was mediated by p38 MAPK and JNK pathways [40]. The level of p-JNK increased in methotrexate (MTX)-treated platelet apoptosis, and it activated Bad and Bax and inhibited Bcl-2, thus, contributing toward mitochondrial dysfunction [41]. Serum-free media could increase the H 2 O 2 production and activate JNK in MLO-Y4 osteocyte-like cells, resulting in cell apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, isoliensinine-induced apoptosis in human breast cancer cells was mediated by p38 MAPK and JNK pathways [40]. The level of p-JNK increased in methotrexate (MTX)-treated platelet apoptosis, and it activated Bad and Bax and inhibited Bcl-2, thus, contributing toward mitochondrial dysfunction [41]. Serum-free media could increase the H 2 O 2 production and activate JNK in MLO-Y4 osteocyte-like cells, resulting in cell apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…The suspended platelets in each group were pre-treated with a 1-mM dose of the ROS scavenger N-acetylcysteine (NAC) (Sigma-Aldrich, USA) [28], a 0.2-μM dose of the mTOR inhibitor Rapamycin (Sigma-Aldrich, USA) [16] or a 1-mM dose of the autophagy inhibitor 3-MA (Sigma-Aldrich, USA) [16] for 30 min, and then 50 μg/ml ox-LDL was added to platelets and incubated for 10 min.…”
Section: Grouping and Treatment Of Washed Plateletsmentioning
confidence: 99%
“…Recently emerging evidence confirmed NACA as a protective agent against oxidative stress in vitro and in vivo [1316]. Our previous study also indicated NACA could protect renal tubular epithelial cell against contrast-induced apoptosis in vitro [6].…”
Section: Introductionmentioning
confidence: 78%